Cultural heritage of a poster: communicative and creative experience - Pryshchenko, Svitlana Valeriivna (Creativity Studies, 2021)
This study contributes to the history of poster connected with interdisciplinary conceptualization, where poster is examined as a design object and core advertising medium in the context of cross-cultural interaction, cultural integration and national identification. Artistic and stylistic features of famous poster schools (Swiss, German, Austrian, Polish, Japanese, French, Italian, Baltic, Ukrainian, etc.) are analyzed and theoretically summarized on the example of cultural-imagery and tourist posters from different countries. Communicative and aesthetic aspects of image creation are presented in socio-cultural dynamics according to certain stages of social development. Colour is highlighted as the most important and attractive means among compositional factors. Scientific novelty of this study is to justify the world’s cultural heritage of poster. It is proved that poster actively shapes public consciousness and has a powerful influence on public opinion. Also, poster is included in social sign system and represents past or present creative experience. Semantic role of poster is a visualization of relevant idea, general rendering of advertised object in visual form and content, perfect reflection of real or imaginary objects and phenomena in mind. The results of study indicate that present-day poster, as a product of culture should have accentuated aesthetics, non-standard vision, and variability of graphic communication and be interesting for the target audience. As advertising often borrows images from different arts, their creative interpretation and preservation of symbolic meanings are of great importance. Particular attention is focused on the relationship between art imagery and functionality in the process of poster designing.